112k views
0 votes
Solve the equation a = m – n for the variable m.

User SCouto
by
5.2k points

2 Answers

0 votes

Answer:


\rightsquigarrow\quad\sf{m=a+n}

In-depth explanation:

Hi there, let's solve this equation.

Let's rearrange the equation a = m - n for m.

m - n = a

Add n to each side:

m = a + n

Therefore, m = a + n.

User Mathinvalidnik
by
5.4k points
3 votes
M = a+n
you would need to add variable n to both side in order to get variable m by itself :))
Solve the equation a = m – n for the variable m.-example-1
User Richard Nixon
by
5.7k points